2010
DOI: 10.1038/nature09605
|View full text |Cite
|
Sign up to set email alerts
|

Cap binding and immune evasion revealed by Lassa nucleoprotein structure

Abstract: Summary Lassa fever virus (LASV) causes thousands of deaths yearly and is a biological threat agent, for which there is no vaccine and limited therapy1. The nucleoprotein (NP) of LASV plays essential roles in viral RNA synthesis and immune suppression2-6, the molecular mechanisms of which are poorly understood. Here, we report the crystal structure of LASV NP at 1.80 Angstrom resolution, which reveals N- and C-domains with structures unlike any of the reported viral NPs7-10. The N domain folds into a novel str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
397
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 243 publications
(415 citation statements)
references
References 48 publications
12
397
1
1
Order By: Relevance
“…Interestingly, the paper by Qi and colleagues also reported that both trimeric and hexameric forms of LASV NP can degrade dsDNA, whereas they did not comment on which part of the LASV NP is responsible for this DNase activity (18). The similar enzymatic activity of the CCHFV and LASV nucleoproteins raises the possibility that the function of (−)ssRNA virus nucleoproteins is more complex than previously anticipated.…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…Interestingly, the paper by Qi and colleagues also reported that both trimeric and hexameric forms of LASV NP can degrade dsDNA, whereas they did not comment on which part of the LASV NP is responsible for this DNase activity (18). The similar enzymatic activity of the CCHFV and LASV nucleoproteins raises the possibility that the function of (−)ssRNA virus nucleoproteins is more complex than previously anticipated.…”
Section: Discussionmentioning
confidence: 64%
“…Qi and colleagues presented the first full-length LASV NP structure and proposed that the full-length LASV NP contains an RNA-specific 3′-5′ exonuclease activity (18). This exonuclease activity was confirmed by an independent group who located this function to the C-terminal domain (16).…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations